The courage to advocate: How two professions approach public advocacy work. - Watling, Christopher; Sandomierski, David; Poinar, Sophie; Shaw, Jennifer; LaDonna, Kori (Medical Education, 2024)
Background: While health advocacy is an established physician role, most of the educational attention to advocacy has been at the individual patient level. Public advocacy—efforts to effect change at the level of communities, populations or society—remains a poorly defined concept whose educational foundation is underdeveloped. To enrich our understanding of public advocacy, we explored how professionals in two disciplines—medicine and law—have approached its tasks and experienced its challenges. Methods: Using constructivist grounded theory, we interviewed 18 professionals (nine physicians, eight lawyers and one qualified in both disciplines) who engage in public advocacy. We used constant comparison throughout an iterative process of data collection and analysis to develop an understanding of what it means to be a professional in the public domain. Results: Public advocacy work occurs at the intersection of personal and professional identities. Lawyers perceived public advocacy as an embedded element of their professional identity, while physicians more often viewed it as outside their core professional scope. Nonetheless, professional identity influenced how both groups conducted their work. Physicians were more likely to draw on professional attitudes (e.g. their orientation towards evidence and their trusted social position), while lawyers were more likely to draw on professional skills (e.g. building an argument and litigating test cases). The work requires courage and often demands that individuals tolerate personal and professional risk. Conclusion: While medicine has enshrined advocacy in its competency frameworks, it is the legal profession whose practitioners more fully embrace advocacy as intrinsic to professional identity, suggesting that roles are difficult to engineer or impose. Collaboration across public‐facing professions like medicine and law creates opportunities to reimagine public advocacy, to identify the skills required to do it well and to refresh educational strategies. Public advocacy is high‐stakes work. This paper explores how doctors and lawyers navigate this often‐risky activity and speculates on what medicine might learn from law.